Putting the "Family" Back Into Family Therapy. Issue 3 (20th June 2014) - Breunlin, Douglas C.; Jacobsen, Elizabeth
<x xml:space="preserve">Abstract</x> In this article, we examine the field of family therapy by drawing a distinction between two forms of practice: Whole Family Therapy (WFT), defined as treating the whole family, and Relational Family Therapy (RFT), defined as working with a subsystem of the family or an individual while retaining a systemic lens. Our thesis is that the practice of WFT has been in decline for some time and steps must be taken to keep it from becoming a defunct practice. We consider the trajectory of WFT and RFT throughout the development of family therapy through reference to the people, the literature, training, and practice patterns associated with family therapy. We remind the reader of the many benefits of WFT and suggest that today WFT is likely to be practiced in conjunction with RFT and individual therapy. Since training of family therapists today is largely located in degree‐granting programs, we identify constraints to including WFT in such programs. We conclude by offering suggestions that can enhance a program's ability to train students in WFT.